Effect of exposure to aldehyde C9 (nonanal) on the electroencephalographic activity of humans according to time series analysis - Kandhasamy Sowndhararajan, Minju Kim, Songmun Kim (Journal of Applied Pharmaceutical Science, 2023)
Aldehyde C9 (nonanal) is naturally found in various essential oils and is mainly used for rose-like fragrances in perfumery products. This study aimed to evaluate the effect of exposure to aldehyde C9 odor on the electroencephalographic (EEG) activity of humans in relation to time series analysis. Healthy volunteers, 10 men and 10 women, were used for the EEG study. The EEG recording was done using eight-channel electrodes. The EEG measurement was conducted for a total of 30 seconds during the exposure to no odor and C9 odor, and recorded EEG data were examined for every second. In the results, only absolute mid-beta wave activity significantly changed at the left parietal region (8.8988– 7.7534 μV2) for a total of 30 seconds analysis time. However, exposure to C9 odor produced significant changes in absolute wave activity at specific times during time series analysis except for absolute gamma. Furthermore, C9 odor affects the prefrontal (Fp1 and Fp2) and frontal (F3 and F4) regions when compared with temporal (T3 and T4) and parietal (P3 and P4) regions. Based on the results, it could be concluded that C9 odor greatly alters the EEG activity of humans in terms of analysis time.
Keywords: C9, electroencephalography, fragrance, nonanal, olfaction